Association of muscle wasting with mortality risk among adults: A systematic review and meta‐analysis of prospective studies - Huan‐Huan Zhou; Yuxiao Liao; Zhao Peng; Fang Liu; Qi Wang; Wei Yang (Wiley, 2023)
Abstract The relationship between muscle wasting and mortality risk in the general population remains unclear. Our study was conducted to examine and quantify the associations between muscle wasting and all‐cause and cause‐specific mortality risks. PubMed, Web of Science and Cochrane Library were searched until 22 March 2023 for main data sources and references of retrieved relevant articles. Prospective studies investigating the associations of muscle wasting with risks of all‐cause and cause‐specific mortality in the general population were eligible. A random‐effect model was used to calculate the pooled relative risk (RR) and 95% confidence intervals (CIs) for the lowest versus normal categories of muscle mass. Subgroup analyses and meta‐regression were performed to investigate the potential sources of heterogeneities among studies. Dose-response analyses were conducted to evaluate the relationship between muscle mass and mortality risk. Forty‐nine prospective studies were included in the meta‐analysis. A total of 61 055 deaths were ascertained among 878 349 participants during the 2.5‐ to 32‐year follow‐up. Muscle wasting was associated with higher mortality risks of all causes (RR = 1.36, 95% CI, 1.28 to 1.44, I2 = 94.9%, 49 studies), cardiovascular disease (CVD) (RR = 1.29, 95% CI, 1.05 to 1.58, I2 = 88.1%, 8 studies), cancer (RR = 1.14, 95% CI, 1.02 to 1.27, I2 = 38.7%, 3 studies) and respiratory disease (RR = 1.36, 95% CI, 1.11 to 1.67, I2 = 62.8%, 3 studies). Subgroup analyses revealed that muscle wasting, regardless of muscle strength, was significantly associated with a higher all‐cause mortality risk. Meta‐regression showed that risks of muscle wasting‐related all‐cause mortality (P = 0.06) and CVD mortality (P = 0.09) were lower in studies with longer follow‐ups. An approximately inverse linear dose-response relationship was observed between mid‐arm muscle circumference and all‐cause mortality risk (P < 0.01 for non‐linearity). Muscle wasting was associated with higher mortality risks of all causes, CVD, cancer and respiratory disease in the general population. Early detection and treatment for muscle wasting might be crucial for reducing mortality risk and promoting healthy longevity.